Species diversity of small mammals at Gunung StongState Park, Kelantan, Malaysia - Jayaraj V.K; Nurul Farah Diyana Ahmad Tahir; Noor Amirah Udin; Noor Farahin Kamarul Baharin (2012)
A recent small mammal survey was conducted in Gunung Stong State Park. Standard mist nets, harp traps and cage traps were used to document diversity of small mammals in this new protected area. This study reports five new distributional records of bats in Gunung Stong State Park and a first record of Myotis muricola in Kelantan. The study also shows that Gunung Stong State Park is one of the three areas in Peninsular Malaysia where all four Cynopterus species that can be found in Peninsular Malaysia coexist. This protected area also has Maxomys rajah, M. whiteheadi and Niviventer cremoriventer which are currently listed as Vulnerable, highlighting this location as an important conservation area for small mammals. Continuous surveys are needed as information of small mammal diversity in Kelantan is still scarce, and this study is a part of a series of small mammal surveys that have been carried out in Kelantan.